Clopidogrel in addition to aspirin reduces in-hospital major cardiac and cerebrovascular events in unselected patients with acute ST segment elevation myocardial - Zeymer, Uwe; Gitt, Anselm K; Jünger, Claus; Bauer, Timm; Koeth, Oliver; Heer, Tobias; Mark, Bernd; Zahn, Ralf; Gottwik, Martin; Senges, Jochen (Thrombosis and Haemostasis, 2008)
We sought to assess the effect of clopidogrel on in-hospital events in unselected patients with acute ST elevation myocardial infarction (STEMI). In a retrospective analysis of consecutive patients enrolled in the Acute Coronary Syndromes (ACOS) registry with acute STEMI we compared outcomes of either adjunctive therapy with aspirin alone or aspirin plus clopidogrel within 24 hours after admission. A total of 7,559 patients were included in this analysis, of whom 3,541 were treated with aspirin alone, and 4,018 with dual antiplatelet therapy. The multivariable analysis with adjustment for baseline characteristics and treatments showed that the rate of in-hospital MACCE (death, non-fatal reinfarction, non-fatal stroke) was significantly lower in the aspirin plus clopidogrel group, compared to the aspirin alone group in the entire cohort and all three reperfusion strategy groups (entire group odds ratio 0.60, 95% CI 0.49–0.72, no reperfusion OR 0.69,95% CI 0.51–0.94,fibrinolysis OR 0.62,95% CI 0.44–0.88, primary PCI OR 0.54, 95% CI 0.39–0.74).There was a significant increase in major bleeding complications with clopidogrel (7.1% vs. 3.4%, p<0.001). In clinical practice early adjunctive therapy with clopidogrel in addition to aspirin in patients with STEMI is associated with a significant reduction of in-hospital MACCE regardless of the initial reperfusion strategy. This advantage was associated with an increase in major bleeding complications.
Keywords: Clopidogrel; reperfusion therapy; primary percutaneous coronary intervention; ST elevation myocardial infarction; prognosis; clinical practice